KEDUDUKAN HAK WARIS BAGI DAHA TUA PADA MASYARAKAT ADAT BALI DESA KELUSA - Nathania Valerie Wijaya; J.M. Atik Krustiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research method used in this study is a normative juridical method with a statutory and conceptual approach. This paper raises the case of inheritance rights problems faced by old people, specifically in Kelusa Village, Bali, carried out by DW (male) who did not accept if the inheritance in the form of 21 (twenty-one) pieces of land belonging to the RT's parents was given to the RT who holds the position of old people. The results of this study indicate that the RT as old people has inheritance rights to the inheritance of his parents, on the condition that the old people have been confirmed as male (sentana rajeg). This is based on the awig-awig of Kelusa Village, especially in Palet 4 Pawos 69 (1).